Working memory and school readiness in preschool children with sickle cell disease compared to demographically matched controls. (20th October 2022) - Heitzer, Andrew M.; Schreiber, Jane E.; Yuan, Xiaomeng; Wang, Fang; Pan, Haitao; Graff, J. Carolyn; Murphy, Laura; Rupff, Rebecca; Russell, Kathryn; Wang, Winfred; Estepp, Jeremie H.; Hankins, Jane S.; et al.
Summary: Children diagnosed with sickle cell disease (SCD) are at risk of the development of neurobehavioural problems early in life. Specific impairments in executive function skills, including working memory, have been documented in school‐aged children with SCD. These executive skills are known to strongly contribute to early academic skills and preparedness for entering kindergarten. This study examined working memory and school readiness in preschool children with SCD compared to a healthy control group matched for race, sex and parent education. A total of 84 patients diagnosed with SCD (61.9% haemoglobin [Hb]SS/HbSβ 0 ‐thalassaemia) and 168 controls completed testing. The mean (SD) ages of patients and controls at testing were 4.53 (0.38) and 4.44 (0.65) years respectively. The SCD group performed worse than controls on measures of executive function, working memory and school readiness ( p < 0.01; Cohen's D range: 0.32–0.39). Measures of working memory were associated with school readiness after accounting for early adaptive development. Multiple linear regression models among patients diagnosed with SCD revealed that college education of the primary caregiver was positively associated with school readiness ( p < 0.001) after controlling for sex, genotype, age and early adaptive development. These results highlight the need to implement school readiness interventions in young children diagnosed with SCD emphasising executive function skills.